Sharp Power Mean Inequalities for the Generalized Elliptic Integral of the First Kind - Wang, Miao-Kun; He, Zai-Yin; Chu, Yu-Ming (Computational methods and function theory, 2020)
We establish two sharp inequalities involving the power mean and generalized elliptic integral of the first kind. As applications, the analogous inequalities concerning the complete p -elliptic integral of the first kind are also derived.